Pengukuran Produktivitas dengan Metode Overal Equipment Effectiveness dan OMAX di Lini Produksi TMM1 dan TMM2 PT. MTG - Magdalena, Riana; Negara, Delima Permata (Metris: Jurnal Sains dan Teknologi, 2019)
PT MTG is a company engaged in the gears and mechanical part component. In the current condition, PT MTG has an effort to improve the company's work efficiency through with an efficiency target of 80%. However, the current problem is that the company does not yet have the right method for evaluating and detecting factors that inhibit increased productivity on the "TMM 1" and "TMM 2" production lines. To find out the right method for PT MTG, two productivity measurement methods are used in total with the Overall Equipment Effectiveness (OEE) method and partially with the Objective Matrix (OMAX) method. In measuring productivity with the OEE method, it can be seen six big losses that occur in each machine on each production line. Whereas in the OMAX method, measurement of productivity is used 4 criteria to determine the company's productivity index, namely (1) Minimization of Defective Products; (2) Optimizing Production Capacity; (3) Efficient Use of Labor; (4) Minimize Absence of Work. Based on the results of data processing and analysis, the average overall OEE value for the "TMM 1" and "TMM 2" production lines is 0.32% and 0.321%. The OEE value still does not meet the JIPM standard of 85%. Whereas in the OMAX results, the average productivity index value of the two production lines is 140.80 per month from the optimal value of 1000. The factor influencing the two methods for not achieving the target is the amount of production per month that differs more than 55% of the production plan. Whereas in OEE, excess production is not considered a loss. So, for the current conditions the right method of measuring productivity for PT MTG is the OMAX Method.